2017
DOI: 10.1080/15592294.2016.1248007
|View full text |Cite
|
Sign up to set email alerts
|

De novo methylation in male germ cells of the common marmoset monkey occurs during postnatal development and is maintained in vitro

Abstract: The timing of de novo DNA methylation in male germ cells during human testicular development is yet unsolved. Apart from that, the stability of established imprinting patterns in vitro is controversially discussed. This study aimed at determining the timing of DNA de novo methylation and at assessing the stability of the methylation status in vitro. We employed the marmoset monkey (Callithrix jacchus) as it is considered the best non-human primate model for human testicular development. We selected neonatal, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 40 publications
2
23
0
Order By: Relevance
“…Thus, defining the timing of establishment of DNA methylation throughout testicular development is crucial to investigate factors that can lead to disturbances of this process, as disease or exposure to treatments. While the majority of studies in the mouse model have shown perinatal acquisition of germ cells' DNA methylation [48,49], in non-human primates (marmoset) establishment of methylation was suggested to be a gradual process occurring during postnatal development and completed in adulthood [39]. In agreement with the primate data, our results show that in human, testicular tissue establishment of global DNA methylation of spermatogonia occurs progressively during postnatal and pubertal development.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Thus, defining the timing of establishment of DNA methylation throughout testicular development is crucial to investigate factors that can lead to disturbances of this process, as disease or exposure to treatments. While the majority of studies in the mouse model have shown perinatal acquisition of germ cells' DNA methylation [48,49], in non-human primates (marmoset) establishment of methylation was suggested to be a gradual process occurring during postnatal development and completed in adulthood [39]. In agreement with the primate data, our results show that in human, testicular tissue establishment of global DNA methylation of spermatogonia occurs progressively during postnatal and pubertal development.…”
Section: Discussionsupporting
confidence: 86%
“…Immunohistochemical analysis of 5-methylcytosine (5mC) revealed a progressive increase with development. Specifically, neonatal spermatogonia were predominantly unmethylated (27 ± 1.5% of methylated spermatogonia), then methylation of the spermatogonial population rose during prepubertal (39 ± 23%) and pubertal (83 ± 7.9%) stages until nearly all adult spermatogonia (97 ± 1.7%) were methylated [39].…”
Section: Introductionmentioning
confidence: 99%
“…There has been discussion in literature regarding the stability of germ cell DNA methylation patterns and the role of somatic contamination in the analyzed cell fractions. A recent study in marmoset monkey revealed stable DNA methylation patterns of the H19, MEST, DDX4 and MAGEA4 genes in germ cells cultured up to 21 days [72]. Since we detected differential methylation of GO-terms related to germ cell development and in particular DNA methylation regulation of germ cell formation, there could be differences in the functionality or cellular composition of the cultured cell fractions between human and marmoset/rodent germ cell cultures.…”
Section: Plos Onementioning
confidence: 48%
“…Therefore, the methylation patterns in genic features and CpG islands of pig testis were investigated to reveal significant cytosines and associated genes for epigenetic molecular mechanisms related to male fertility. Langenstroth-Röwer et al (2017) used the marmoset monkey as the human model for testicular methylation study. They found that cytosines were predominantly unmethylated at regulatory regions of H19, LIT1, SNRPN, MEST , and OCT4 in the germ cells.…”
Section: Discussionmentioning
confidence: 99%